2013
DOI: 10.1053/j.ackd.2012.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Acid Load: A Novel Nutritional Target in Chronic Kidney Disease?

Abstract: Nonvolatile acid is produced from the metabolism of organic sulfur in dietary protein, and the production of organic anions during the combustion of neutral foods. Organic anion salts that are found primarily in plant foods are directly absorbed in the gastrointestinal tract and yield bicarbonate. The difference between endogenously produced nonvolatile acid and absorbed alkali precursors yields the dietary acid load, technically known as the net endogenous acid production, and must be excreted by the kidney t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
192
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(203 citation statements)
references
References 109 publications
4
192
1
6
Order By: Relevance
“…23 Conversely, plant-based proteins (e.g., soy and legumes) and fruits and vegetables have a high basal load. 24 Therapy with alkali has been shown to slow the progression to ESRD in randomized controlled trials. 25 Published data have shown that red meat generally yields greater acid production than other animalsourced protein, although the difference is not that dramatic.…”
Section: Discussionmentioning
confidence: 99%
“…23 Conversely, plant-based proteins (e.g., soy and legumes) and fruits and vegetables have a high basal load. 24 Therapy with alkali has been shown to slow the progression to ESRD in randomized controlled trials. 25 Published data have shown that red meat generally yields greater acid production than other animalsourced protein, although the difference is not that dramatic.…”
Section: Discussionmentioning
confidence: 99%
“…High NEAP levels may rapidly lead to kidney disease progression in CKD patients [1,4,5]. NEAP modulation may be a tool for alteration of the glomerular filtration rate decline.…”
Section: Discussionmentioning
confidence: 99%
“…We divided the patients into responders and nonresponders in both the intensive- and the conventional-education groups according to the same standard as above. The NEAP was estimated from the protein/potassium ratio in the diet [11,12] as follows: NEAP (mmol/day) = -10.2 + 54.5 [protein intake (g/day)/potassium intake (mmol/day)] [4,5,11,13]. The daily dietary protein intake was estimated based on the 24-hour urine urea nitrogen excretion using the Maroni equation [protein intake = 6.25 × (urine urea nitrogen + 0.031 × ideal body weight)] [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential renal acid load (PRAL) of selected food items (per 100 g serving) is adapted from estimates performed by Remer and Manz [18,19] . Reprinted, with permission [24] . …”
Section: Disclosure Statementmentioning
confidence: 99%